Energy economics and development - Товма, Н. (Journal of Economic Research & Business Administration, 2017)
In this paper propose to build a system of indicators of greening economy to assess the impact of the energy factor in the value of GDP using economics – mathematic model, reflection the dependence of factor. In particular, most of the strategies for economic growth and development, implemented over the past decades have encouraged rapid accumulation of financial capital opposite a natural capital. Current development model is detrimental to the well-being of generations, creates great risks and challenges for future generations and necessitates the transition to a green economy to achieve sustainable development in the long run. The article noted the recognized world leader in the field of energy and resource savings. In all countries where there are significant advances in addressing the issues of energy efficiency, the decisive role belongs to the state. It is noted that in the Republic of Kazakhstan the development of the legal framework in the field of energy conservation has a positive effect on energy efficiency. How-ever, legislative initiatives are not applied universally, which are advisory in nature, in contrast to the US and EU. The article gives practical recommendations to strengthen the energy efficiency of the work, the diversification of energy sources and the creation of strategic reserves of energy raw materials. The paper suggests possible ways to cover the increasing demand of electricity.